2018
DOI: 10.1515/revecp-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Research and Development (R&D) Investments on Sustainable Economic Growth: Evidence from OECD Countries (1996-2015)

Abstract: This study is devoted to the empirical analysis by second generation panel data analysis of the effects of the R&D investment variables in different qualifications in OECD countries grouped as OECD-20 and OECD-9 based on the income levels of the economic growth for the period of 1996-2015. Within this context, the purpose of this study is to evaluate whether or not the economic growth performances of OECD-20 and OECD-9 countries have a sustainable structure that endogenizes the technological advancements a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 31 publications
0
10
0
2
Order By: Relevance
“…This result is in accordance with [ 52 ]’s work in assessing the nexus between CO 2 emissions, economic growth, urbanization, and energy consumption in Belt and Road economies. Similarly to [ 53 ]’s work in OECD, where they unveiled the effects of research and development on economic growth. In this study, [ 53 ] identified the presence of long-term association among their selected variables.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in accordance with [ 52 ]’s work in assessing the nexus between CO 2 emissions, economic growth, urbanization, and energy consumption in Belt and Road economies. Similarly to [ 53 ]’s work in OECD, where they unveiled the effects of research and development on economic growth. In this study, [ 53 ] identified the presence of long-term association among their selected variables.…”
Section: Discussionmentioning
confidence: 99%
“…Fundamentally speaking, total factor productivity measures the influence of factors such as technological innovation, process improvement, management level, and efficiency. e role of industrial organization in economic development reflects the quality of economic development and represents the overall efficiency of the use of input factors [21].…”
Section: Tfpmentioning
confidence: 99%
“…As technology improves with the investments of companies, growth proceeds at the firm and industry level. Some research approves the positive relationship between R&D and sustainability (Alam et al, 2019;Yazgan & Yalçınkaya, 2018). R&D is a kind of trigger for innovations pertaining to different areas.…”
Section: Empirical Studiesmentioning
confidence: 99%